A systematic literature review about dimensioning safety stock under uncertainties and risks in the procurement process - Júlio Barros; Paulo Cortez; Maria S. Carvalho (Operations Research Perspectives, 2021)
This paper analyses literature contributions in the search for safety stock problem under uncertainties and risks in the procurement process, focusing on the dimensioning problem (determination of the safety stock level). We perform a systematic literature review (SLR) from 1995 to 2019 in relevant journals, covering 193 selected articles. These selected articles were classified into three safety stock main issues: safety stock dimensioning, safety stock management, and safety stock positioning, allocation or placement. The SLR analysis allowed the identification of literature gaps and research opportunities, thus providing a road map to guide future research on this topic.
Keywords: 330; Safety stocks; Inventory management; Procurement; Supply chain risk management; Uncertainty factors; Systematic literature review